Automated Analysis of Slow Crack Growth in Hydrous Soda-Lime Silicate Glasses - Kiefer, Philipe; Maiwald, Martin; Deubener, Joachim; Balzer, Robert; Behrens, Harald; Waurischk, Tina; Reinsch, Stefan; Müller, Ralf (Frontiers in Materials, 2020)
To explore the impact of ambient and structural water on static fatigue, the initiation and growth of 3279 Vickers induced median radial cracks were automatically recorded and analysed. We find that humidity is more efficient in initiating cracks and promoting their growth than water, which is dissolved in the glass structure. In particular for slow crack growth (< 3  10-6 m s-1), tests in dry nitrogen showed a considerable decrease in the crack growth exponent with increasing water content of the glasses. On the other hand, if tests were performed in humid air, the crack growth exponent was independent of the water content of the hydrous glasses, while stress intensity decreased slightly. These observations indicate that water promotes the processes at the crack-tip regardless of its origin. However, ambient water is more efficient.